Civil Political Development in Local Democracy - Rattana, Thawan; Phongphitakyotin, Thanison; Maiphranate, Pattaradanai; Dokchan, Phasakorn (Interdisciplinary Academic and Research Journal, 2023)
Politics, elections, and local democracy are fundamentally democratic or Thailand's foundational democracy because it is an important channel for local people to have space to express their opinions, complaints, and presentations of their needs to representatives in local government organizations which may be overlooked Therefore, this article aims to study 1. Principles and importance of local elections. which is a process for electing representatives at the local level according to democratic principles; and 2. development of regional politics. citizens that affect democracy at the local level by relying on documents, textbooks, academic articles, and related research, etc., by explaining the dynamics of Thai political culture at the local level, principles, and the importance of local elections. The relationship between local politics and national politics and local political development in Thailand. To develop civil society and democracy at the local level It is the fundamental democracy of the country. to the development of politics, elections, and democracy at the local level. The results of the study revealed that the development of civil politics in democracy at the local level focuses on selecting representatives to manage public services to meet the needs of the people. It has an important duty to support development and provide opportunities for the participation of the local people, which requires cooperation and development in parallel between the people and local government organizations in civic politics development in the local democratic system. There are 7 components as follows: (1) Promotion of democratic education at the local level. (2) Issuing policies to allow the public to participate in the process. (3) Increasing the power of mass communication and opening channels for political communication at the local level. (4). Increasing the power of monitoring, auditing, and evaluating the work of local politicians from the people's sector. (5). Reduce the influence and role of the leader in Serve during the election period. (6). Development support. Human resources in local democratic communities. And (7) Human resource development processes at the community local level to develop people's politics in the local democratic system to achieve goals with efficiency and sustainability.